The second century : reconnecting customer and value chain through build-to-order : moving beyond mass and lean production in the auto industry - Holweg, Matthias (MIT Press, 2004)
As the auto industry moves into its second century, it suffers from low margins and a sclerotic value chain that cannot evolve with customer desires. Inventories of many weeks pile up on dealer lots and at distribution centers around the world while executives applaud marginal improvements in factory efficiency. Value streams based on Henry Ford's mass-production model from the early 1900s do not deliver the strategic flexibility that is needed in today's increasingly competitive and demanding market. With billions of potential product variations, customers still compromise by selecting from a limited number of products sitting at dealerships or at distribution centers. Those customers who dare insist on a specific variation not only wait weeks but also pay extra for the privilege of telling vehicle manufacturers what they actually want. In The Second Century, Matthias Holweg and Frits Pil provide a comprehensive look at today's dysfunctional value-chain strategies, then systematically discuss the changes in products and in processes that are needed to bring about responsiveness to customer needs through build-to-order. They look beyond the dealer, the factory and the design studio to examine the web of relationships and dynamics that have brought the auto industry to its current low point. Holweg and Pil argue that in this century the winners will not be those firms that search for larger and larger scale or those who run efficient factories, or those that squeeze the last drop of profitability from their suppliers. The winners, they say, will be those who build products as if customers mattered.